(untitled) (Encuentros, 2023)
The ideals of beauty are a construct in which the family, culture, society and the media intervene, in an interweaving that ultimately determines the woman’s bodily satisfaction. This reflection article derives from the theoretical and contextual review of the research “Female viewers’ processing of contravening beauty ideals in movie melodrama in Mexico and Colombia and their body esteem responses: an exploratory study” project carried out between the University of Athabasca (Canada), the University of the Gulf of California (Mexico) and the Catholic University Luis Amigó (Colombia) and presents, based on the studies found in the context of Latin America, how the beauty ideals of women in the continente are influenced by the media and their impact on the body satisfaction of Latin American women. In conclusion, it is evident that there is a relationship between the media uses of women and the construction of their ideals of beauty, which affects a greater dissatisfaction with their bodies. It highlights the impact of the thin ideal on women’s body satisfaction and how it influences eating disorders, sports behavior, surgery, and mental health conditions. Although there are important research contributions in Latin America on the subject, further study is required on the social determinants in the construction of beauty ideals and the contribution of the media to them.